Pengaruh karakteristik komite audit terhadap fraudulent financial reporting - Gading Ruchiatna; Pratana Puspa Midiastuty; Eddy Suranta (Penerbit Goodwood, 2020)
Purpose : This study aimed to prove whether audit committees were proxied financial expertise and meetings related to fraudulent financial reporting. Research methodology: This type of research was quantitative descriptive with an evaluation model of Beneish M-Score and Altman Z-Score in predicting fraudulent financial reporting. The sample in this study was non-financial companies listed on the Stock Exchange with an observation period of 2010-2018. The technique of taking samples with purposive sampling obtained the number of observations 551. Data processing was done via SPSS through logistic regression. Results : The results of the study showed that the characteristic of the audit committee that influence the fraudulent financial reporting is financial expertise possessed by the members of the audit committee, while the number of audit committee meetings has no effect on the fraudulent financial reporting. Limitation: This study only used a sample of non-financial companies listed on the Indonesia Stock Exchange in 2010-2018 and met the criteria. The dependent variable fraudulent financial reporting measured through the Beneish M-Score and Altman Z-Score models. The independent variable was financial and or accounting expertise from the members of the audit committee and the Audit Committee Meeting. Contribution: Investors can consider this research in making decisions to be more careful in investing, as well as a reference for further research. The results of this study are expected to provide an overview and understanding of the role of the audit committee in suppressing fraudulent financial reporting using the Beneish M-Score and Altman Z-Score. Keywords: Fraudulent financial reporting, Audit committee characteristics, Leverage